E-Learning Within the Framework of the Czech University System - Klement, Milan; Dostál, Jiří (Revija za elementarno izobraževanje, 2013)
During the last few years, e-learning has become an integral part of tertiary education systems, not only within the framework of blended, but, to an increasingly larger extent, also of full-time study modes, accredited and implemented at Czech universities. However, along with its large-scale deployment, a number of problems have emerged, which resulted in the formulation of new research hypotheses. Among the most important ones are those regarding the influence of e-learning on the quality of education, the efficient ways of motivating and mobilizing students, and the creation and development of particular competences. There are many external, as well as internal influencing factors, acting more or less covertly, to a greater or lesser intensity. It is highly desirable to identify, describe, analyze, and minimize or maximize their influence in order to prevent them from having a massive negative impact, conditioned by fashion trends, on the quality of tertiary education.